Recent advances in engineering fast-growing cyanobacterial species for enhanced CO2 fixation - Kim, David S.; Moreno-Cabezuelo, José Ángel; Schulz, Eduardo Nicolas; Lea-Smith, David J.; Sagaram, Uma Shankar (Frontiers in Climate, 2024)
Atmospheric CO2 removal (CDR) is a fundamentally endergonic process. Performing CDR or Bioenergy with Carbon Capture and Storage (BECCS) at the gigatonne scale will produce a significant additional burden on the planet's limited renewable energy resources irrespective of the technology employed. Harnessing photosynthesis to drive industrial-scale CO2 fixation has been of significant interest because of its minimal energy requirements and potential low costs. In this review, we evaluated the thermodynamic considerations of performing atmospheric carbon removal using microalgae and cyanobacteria versus physicochemical processes and explore the implications of these energetic costs on the scalability of each respective solution. We review the biomass productivities of recently discovered fast-growing cyanobacterial strains and discuss the prospects of genetically engineering certain metabolic pathways for channeling the fixed carbon into metabolic 'carbon sinks' to further enhance their CO2 capture whilst concurrently extracting value. We share our perspectives on how new highly productive chassis strains combined with advanced flux balance models, essentially coupling synthetic biology with industrial biotechnology, may unlock more favorable methods for CDR, both from an economic and thermodynamic perspective.